MADRASAH NIZHAMIYAH DALAM PERSPEKTIF POLITIK PENDIDIKAN ISLAM: ANALISIS HISTORIS DAN IMPLIKASI SOSIO-INTELEKTUAL - Siti Yusrona Daulay; Zainal Efendi Hasibuan; Erik Novianto (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2025)
The Nizamiyah Madrasah, founded in the 11th century CE by Nizam al-Mulk the prime minister of the Seljuk Dynasty has been a pivotal point in the history of ancient Islamic education. The institution not only contributed to the development of Islamic science, but also served as a strategic tool in the political agenda of power. This research aims to analyze the relationship between education and politics through a literature study with a historical analysis approach. The main findings show that the establishment of the Nizamiyah Madrasah served as a state tool to strengthen the political legitimacy of the Seljuk Dynasty, disseminate Sunni ideology systematically, and limit the influence of opposition groups such as Shia and other schools of thought that were considered deviant. The main contribution of this study lies in understanding how classical Islamic educational institutions were utilized as tools for the consolidation of power and the domination of state ideology.